Short Position Disclosures and Underlying Stock Performance: Evidence from Polish Stock Market - Dadej, Mateusz (Journal of Finance and Financial Law, 2020)
After introducing EU Regulation on short selling and certain aspects of credit default swaps, in 2012, investors holding a significant short positions are obliged to disclose it in a public manner, through the local supervisor registry. Beside the intended transparency, such a registry also have a cogent influence on behaviour of market participants. The Multimillion euros worth of short position is a strong view on underlying stock perspective, to say the least. Thus, many investors do care about the public disclosures of short positions and some of them manage their portfolios accordingly. The aim of herein paper is to provide quantitative assessment of stock performance following short position announcement and present activity of short selling investors on Polish stock market. The research hypothesis verified in this study stated that the prices of short sold stocks are exhibiting significant downward trend relative to the benchmark in a half a year period after disclosure.